Posterior Reversible Encephalopathy Syndrome After Self-Medication With an Oral Decongestant: A Case Report - Zerbib, Yoann; Gibert, Louis; Bennis, Youssef; Masmoudi, Kamel; Maizel, Julien; Brault, Clément (Frontiers in Medicine, 2022)
Introduction Posterior reversible encephalopathy syndrome (PRES) is a rare neurological disorder caused by the dysregulation of cerebral perfusion. Case Presentation We report on a 18-year-old female patient with a history of end-stage renal disease and thrice weekly hemodialysis. She was admitted to the emergency department with mental confusion, blurred vision, headaches, and vomiting, following self-medication with an oral decongestant containing pseudoephedrine. We observed hypointense lesions with T1-weighted MRI and hyperintense areas with T2-weighted and fluid-attenuated inversion recovery MRI sequences. The lack of diffusion restriction was consistent with a diagnosis of PRES. A concomitant Enterobacter cloacae hemodialysis catheter-bloodstream infection was also diagnosed. We hypothesize that both sepsis and inappropriate self-medication with oral pseudoephedrine contributed to hypertension, endothelial dysfunction, and vasogenic edema. The patient received intensive care and made a full recovery. Discussion PRES is a life-threatening condition that requires intensive care. Identification of the etiology is the keystone of medical care. Inappropriate self-medication with an oral decongestant might trigger PRES - highlighting the importance of patient education.